Analisis Dampak Variabel Moneter Terhadap Stabilitas Perekonomian Indonesia - Maya Oktavia Resfika; Mike Triani (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the impact of monetary variables on Indonesia’s economic stability during the period 2010Q1-2024Q4 using the Vector Error Correction Model(VECM) method, Variables include GDP growth (proxy for economic stability) and three monetary variables: inflation, the policy interest rate ( BI Rate), and the money supply (M2), Using quarterly time-series data sourced from Bank Indonesia and the Central Bureau Of Statistics (BPS), the results show that: (1) inflation does not significantly affect GDP in the short term but has a long-run relationship through the cointegration mechanism; (2) The BI Rate is proven effective in controlling inflation through the interest rate transmission channel as confirmed by IRF analysis; (3) money supply (M2) has a significant negative effect on GDP in the long run with a coefficient of -1.507; and (4) the Error Correction Term (ECT) of -0.917 indicates that the Indonesian economy has a very strong self-correcting mechanism of 91.7% per quarter. The FEVD result show that inflation contributes the most to GDP variation among monetary variables (15% by period ten). The findings reinforce both the Quantity Theory of Money and the IS-LM transmission framework, and imply sustained commitment to Indonesia’s Inflation Targeting Framework.